Pembelajaran berkonsepkan teori konstruktivisme lima fasa Needham dalam persekitaran web 2.0 dan kesannya dalam mata pelajaran sejarah. - Mohamad Fakri, Khairunisa (2013)
This study aims to provide learning environment for History subject by using web 2.0 application and five phase Needham constructivism model. Furthermore, it is also to determine the effect of using web 2.0 application, supported by the five phase Needham constructivism model, in students learning History from their motivational aspect, interest and reflective thinking. This study also determines on how educational technology such as Glogster can help students in learning History subject which focuses more on reflective thinking. There were 25 students with different races involved in this study. The sample consisted of 12 male and 13 female students. Questionnaire and interview were used as the instrument for this study. Data was analyzed by using descriptive statistic like mean, standard deviation and percentage. The interview was analyzed based on theme. The reliability of the instrument in this research was a = 0.92. The results showed that the level of motivation (Mean = 3.64), interest (Mean = 3.53) and reflective thinking (Mean = 3.58)among the students were moderate. The results also showed that by using web 2.0 application such as Glogster, it could help the students to think reflectively